Upaya Peningkatan Pengetahuan Mahasiswa Fakultas Teknik Universitas Muhammadiyah Palu Melalui Pelatihan Pengolahan Air Bersih - Widodo, Eko; Sulfiati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2023)
Processing clean drinking water is a challenge in itself based on the Minister of Health's Regulation on drinking water quality standards No. 492/MENKES/PER/1V/2010 which is usually stated in the form of a statement or number indicating the requirements that must be met so that the water does not cause health problems., disease, technical problems, and aesthetic problems. Through this training, students from the engineering faculty at Muhammadiyah University in Palu are trained to understand how to process clean water suitable for consumption, so that they can provide clean water in sufficient quantities and have maintained quality.